2016
DOI: 10.1016/j.jacc.2016.03.578
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair Compared With Medical Management of Patients With Uncomplicated Type B Acute Aortic Dissection

Abstract: This study confirmed the feasibility of TEVAR for uncomplicated type B aortic dissection in the acute setting with fewer aortic-related adverse events and a lower mortality rate compared with BMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
144
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(152 citation statements)
references
References 35 publications
6
144
1
1
Order By: Relevance
“…Nevertheless, medical treatment is associated with a well-known risk of expansion of distal dissected segments, which occurs as a late complication in about 30-40% of patients (4,5). Preemptive management of so-called uncomplicated TBAD has recently been shown to prevent aneurysmal degeneration and impact positively on survival with a lower incidence of late complications by the induction of remodelling (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, medical treatment is associated with a well-known risk of expansion of distal dissected segments, which occurs as a late complication in about 30-40% of patients (4,5). Preemptive management of so-called uncomplicated TBAD has recently been shown to prevent aneurysmal degeneration and impact positively on survival with a lower incidence of late complications by the induction of remodelling (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…If in doubt, a connective tissue disorder should reliably be ruled out before considering prophylactic TEVAR.How do the present findings fit into the current strategic management of type B aortic dissection and how do these new data add value? A structured follow-up scheme (in any case of dissection) seems valuable considering the relatively high vascular event rate regardless of therapy(7). Further, the data confirmed a long-term benefit from TEVAR in "un-complicated" type B dissection and solidified the notion of prophylactic TEVAR.…”
mentioning
confidence: 60%
“…Thus, if a patient was expected to survive at least 5 years, the evidence suggested that early TEVAR offered an advantage over medical management alone. It should be noted that reported event rates in both groups appear high and underline the need for structured follow-up/surveillance of all patients with previous dissection.The work by Qin et al(7) would seem to confirm the recent swing to dismiss the term "uncomplicated dissection" and consider most, if not all, cases of type B dissection as "potentially complicated," because these patients' outcomes seem to improve long term as previously suggested from registries and the ran-…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Qin et al (1) reported a multi-institutional retrospective study involving three hospitals that analyzed and compared the effects of thoracic endovascular aortic repair (TEVAR) combined with best medical treatment (BMT) versus BMT alone for treating uncomplicated acute type B aortic dissection (TBAD). The controversy regarding the actual efficacy and benefits of TEVAR in uncomplicated acute TBAD is partly attributable to study reports based on analysis over a heterogeneous population of both complicated and uncomplicated TBAD patients (2).…”
mentioning
confidence: 99%